1985
DOI: 10.1002/chin.198536079
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: COPPER(II) BINDING BY SUBSTITUTED 1,3,5‐TRIAZINE HERBICIDES

Abstract: Mittels potentiometrischer Messungen werden die Stabilitätskonstanten der Cu‐Komplexe mit den Triazinherbiziden (I) bestimmt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Displacement of the loosely bound water from the hydrophobic micropore space was believed to be the major mechanism of atrazine sorption on microporous minerals (Cheng and Reinhard, 2007;Hu et al, 2012;Hu and Cheng, 2013a). Due to the presence of heteroatom (N) with free electron pairs and aromatic ring with delocalized p electrons, atrazine molecules have relatively strong interactions with transition metals, such as copper, and form the corresponding complexes (Decock et al, 1985;Grabec et al, 1994). As a result, atrazine could adsorb more strongly on Cu/CBV-720 than on CBV-720.…”
Section: Sites Of Transition Metals In Zeolite Microporesmentioning
confidence: 99%
“…Displacement of the loosely bound water from the hydrophobic micropore space was believed to be the major mechanism of atrazine sorption on microporous minerals (Cheng and Reinhard, 2007;Hu et al, 2012;Hu and Cheng, 2013a). Due to the presence of heteroatom (N) with free electron pairs and aromatic ring with delocalized p electrons, atrazine molecules have relatively strong interactions with transition metals, such as copper, and form the corresponding complexes (Decock et al, 1985;Grabec et al, 1994). As a result, atrazine could adsorb more strongly on Cu/CBV-720 than on CBV-720.…”
Section: Sites Of Transition Metals In Zeolite Microporesmentioning
confidence: 99%
“…Previous studies on interaction of metal ions with pesticides having metal binding sites have shown stable complexed species can be formed, and they may have relevance to metal ion distribution in soil (Decock et al, 1985;Lerivrey et al, 1986;Pusino et al, 1988). Metal ions forming neutral complexed species may be desorbed from clays and replaced by protons or protonated molecules as the saturating cations (Micera et al, 1988;Pusino et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of atrazine for all treatments discussed previously is rapid (60 min); this may be related to the affinity of atrazine for the mineral surfaces 68 at circumneutral pH, followed by its degradation in the presence of H 2 O 2 . The rate of atrazine degradation (20 mg L −1 ) was examined over time (10–70 min at intervals of 10 min).…”
Section: Resultsmentioning
confidence: 90%
“…This was verified by an elution study, as mentioned in the UV spectrophotometric analysis section. For modified MK10 and sand, atrazine molecules can interact relatively strongly with copper, due to the presence of heteroatoms (N) with free electron pairs and aromatic rings with delocalized π electrons 68 . The unmodified MK10 shows only adsorption in the presence and absence of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%